2012
DOI: 10.1080/15459624.2012.683757
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Benefit of the User Seal Check on N95 Filtering Facepiece Respirator Fit

Abstract: The objective of this study was to better understand the benefit of the user seal check step for respirator test subjects in the N95 filtering facepiece respirator donning process. To qualify for the study, subjects were required to pass a standard quantitative fit test on at least one of the three N95 filtering facepiece respirator models: 3M 1860 (cup), 3M 1870 (flat-fold), and Kimberly Clark PFR95-270 (duckbill). Eleven subjects were enrolled and performed a series of abbreviated, quantitative fit tests whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Therefore, the current results may underestimate the passing rate of QNFT. 24 Second, Asian participants' weight (reported here) and facial anthropometries (eg, face length, face width; not reported here) were significantly different from that of non-Asian people, which hence affects the passing rate of QNFT. Such differences might reduce the generalizability of the results but increase the specificity of that to Asian populations.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Therefore, the current results may underestimate the passing rate of QNFT. 24 Second, Asian participants' weight (reported here) and facial anthropometries (eg, face length, face width; not reported here) were significantly different from that of non-Asian people, which hence affects the passing rate of QNFT. Such differences might reduce the generalizability of the results but increase the specificity of that to Asian populations.…”
Section: Discussionmentioning
confidence: 65%
“…Unlike well-controlled internal hospital settings in other regions, these environmental differences may limit the current results in that they are less relevant to other settings but are highly situation-specific results for many hospitals located in subtropical climate regions. Further studies are recommended to replicate the works from Myers et al 23 and Viscusi et al, 24 which examined the effectiveness of the user seal check on improving N95 respirator donning among Asian wearers. Another study may investigate how the change of body weight and facial anthropometries of Asian health care workers contributes to leakage of N95 respirators.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…For the testing without training (D1F, D2F), all 50 subjects donned the FFR and conducted fit test after reading the respirator manufacturer's instructions themselves, including performing and passing a use-seal check [21]. For the testing after training, the researchers instructed the same 50 subjects to don and doff a respirator and to conduct the use-seal check.…”
Section: Methodsmentioning
confidence: 99%
“…A seal check is required by the OSHA standard (the facility was made aware of this), and research has demonstrated that a seal check is beneficial to HCWs who have been previously fit tested. 7 Without a proper seal between the user's face and the respirator, inhaled air may bypass the respirator's filter, putting the user at risk for exposure. 8 Influenza vaccination has been repeatedly demonstrated to be an effective means in protecting patient health, but inoculation rates in the United States have remained low.…”
Section: Elements N %mentioning
confidence: 99%